Family-related Disparities in College Enrollment across the Great Recession. (October 2018) - Cozzolino, Elizabeth; Smith, Chelsea; Crosnoe, Robert L.
The economic crisis of the Great Recession in the late 2000s had implications for the intergenerational transmission of inequality within families. Studying patterns of college enrollment across the Great Recession among U.S. youth from diverse family contexts provides insight into how economic volatility can either compound or undercut the advantages that some parents can give their children. Although college enrollment among 18- to 21-year-olds did not decline during or after the Great Recession, analyses of the National Longitudinal Survey of Youth 1979–Young Adult cohort revealed that this general trend subsumed variability by family history, local economic conditions, and age. Histories of family stability and sufficiency were associated with higher odds of college enrollment over time and across age, but this advantage was largest during the Recession in high-unemployment communities. These results illuminate how life course consequences of early family life can fluctuate with volatility and opportunity in the broader economy.